What Changes the Youth of Southeast Sulawesi (Indonesia) after Living Abroad - Muhammad Kurniawan Rachman (International Journal of Transdisciplinary Knowledge, 2021)
According to Central Bureau Statistic of Southeast Sulawesi, Indonesia, 24.15 % of citizens aged 7 until 24 years old decided to stop pursuing education. This data shows how critical building the willingness of citizens in Southeast Sulawesi to see the world as a competitive game where education takes a vital role. There have been many efforts to solve this problem, one of them is the effort of the country to send people to study abroad by scholarship or fellowship. This research tried to unveil the perspectives of people in Southeast Sulawesi who have experience studying or doing an internship abroad. The study used open-ended questionnaires from fifty alumni of scholarships and fellowships from Southeast Sulawesi. This report tried to unveil alumni stories of experiencing the culture and values and living abroad and how they applied them after returning to the country. In general, they showed positive feedback from the scholarship or fellowship experience they had. However, they perceived some critiques toward some cultures and system after returning to their homeland. Keywords: Youth, Living abroad, Scholarship and Fellowship, Culture.